2013
DOI: 10.1097/sap.0b013e31822f679c
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Reduction Mammaplasty and Pulmonary Functions

Abstract: The hypothesis that weight on the chest may diminish the compliance of the chest wall and affect chest wall dynamics guided this research. Few previous studies investigated the possibility of increasing chest compliance and pulmonary function after reduction mammaplasty. The meager results available were contradictory. The aim of this study was to determine the relation between reduction mammaplasty and pulmonary function. Thirty-three adult female patients who presented for reduction mammaplasty were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
6
1
Order By: Relevance
“…However, a statistically significant difference was not found between preoperative to postoperative pulmonary functions. The differences between the findings in the study by Elhusseiny et al (9) and the present study may be attributed to the timing of lung function measurement, age of the study participants and the weight of breast tissue excised.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…However, a statistically significant difference was not found between preoperative to postoperative pulmonary functions. The differences between the findings in the study by Elhusseiny et al (9) and the present study may be attributed to the timing of lung function measurement, age of the study participants and the weight of breast tissue excised.…”
Section: Discussioncontrasting
confidence: 93%
“…Elhusseiny et al (9) aimed to determine the relationship between reduction mammoplasty and pulmonary function. They found a significant difference between preoperative and postoperative oxygen saturation (P<0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Removal of the excessive weight from the anterior chest wall would facilitate chest movements, and thus would improve chest compliance. 16 The limitation of the study was the use of spirometry alone in the evaluation of pulmonary function. Although spirometry can provide useful diagnostic and screening information and show restrictive or obstructive disease patterns, in some cases it may not be sensitive enough to show abnormalities before extensive and irreversible damage has been done.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, a series of studies have concluded that reduction mammaplasty had positive effects on relieving breathing difficulties 3,42–44 and improving lung function 45 . Theoretically, chest wall compliance is restricted and reduced by heavy and bulky breasts, and chest wall compliance and pulmonary ventilation were improved by reducing the weight in breast mass 46 . According to a recent review by Crittenden et al, 38 breast reduction surgery provides a clinically relevant health benefit.…”
Section: Discussionmentioning
confidence: 99%